2016
DOI: 10.1111/ecc.12510
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of the effectiveness and safety of kinesiology taping in the management of cancer-related lymphoedema

Abstract: Patients with cancer-related lymphoedema (CRL) commonly refuse treatment with bandaging or hosiery because of hot and humid weather conditions. This review aims to determine the effectiveness and safety of kinesiotaping (KT) in the management of CRL compared to compression bandaging or hosiery. A systematic search of the literature was conducted until July 2015. The primary outcomes were reduction in body part volume or circumference and adverse effects of the interventions. The secondary outcomes were subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
3
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 20 publications
2
45
3
6
Order By: Relevance
“…14 17-19 A systematic review with meta-analysis on cancer-related lymphoedema found no significant difference between kinesiology taping and compression therapies for reducing lymph volume. 20 Kinesiology taping was superior to compression for improving lymphoedemarelated symptoms; however, bandaging was associated with higher quality of life. It was also reported that kinesiology taping was associated with skin-related complications in up to 21% of patients.…”
Section: Introductionmentioning
confidence: 97%
“…14 17-19 A systematic review with meta-analysis on cancer-related lymphoedema found no significant difference between kinesiology taping and compression therapies for reducing lymph volume. 20 Kinesiology taping was superior to compression for improving lymphoedemarelated symptoms; however, bandaging was associated with higher quality of life. It was also reported that kinesiology taping was associated with skin-related complications in up to 21% of patients.…”
Section: Introductionmentioning
confidence: 97%
“…There is just one meta-analysis of the efficacy and safety of using taping in patients with lymphedema secondary to malignant neoplasm, which showed that taping appears to be superior to CP in terms of symptoms, but that patients who were treated with CP had better quality of life. 16 There are just five randomized clinical trials on the subject, with significant differences in relation to the method of application of the taping technique. The studies do exhibit consensus that the tape should be applied to the limb with edema.…”
Section: Discussionmentioning
confidence: 99%
“…Neither skin damage or hyperthermia are common, but redness can occur frequently. 16 Taping enables the lymphatic vessels to open, because the skin is lifted, facilitating lymph flow through improved microcirculation, in addition to guiding the lymph to the desired destination. Individual patient differences and daily activities should be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Normal lymphatic drainage plays a key role in the elimination and transfer of waste matter from the body (bilirubin, pigments), and ultimately prevents swelling [2]. Individuals with BCRL have a malfunctioning lymphatic system, which delays lymphatic drainage, causing an abnormal increase of tissue protein and resulting in chronic inflammation, fibrosis, pain, limited range of motion, or paraesthesia [3,4]. This leads to functional disabilities and mental problems, such as anxiety and depression [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Areas with BCRL are reported to have decreased local immune function, result in having a higher risk of infection and inflammation. Therefore, appropriate interventions need to be applied to reduce and prevent BCRL [4,7].…”
Section: Introductionmentioning
confidence: 99%